Avant-Garde Sebagai Ilustrasi Mitos Dewi Sri - Nadia Rachmaya Ningrum Budiono (PANTUN, 2018)
This paper aims to explain the concept of the creation of avant-garde works inspired by the mythical fgure of Dewi Sri in Javanese society in the form of an illustrated fashion. The purpose is to introduce the mythical fgure of Dewi Sri in Java to the modern society. Dewi Sri is a character who is trusted in the Javanese people life. She is identifed with the goddess of rice, the goddess of wealth, the goddess of fertility and prosperity, the goddess of fame and success. She is believed to be able to provide long life, health and lots of children. She is the mother of life on earth. Avant-garde is one type of artwear or wasable-art focusing on an aesthetic value rather than a function. The research is conducted by collecting literature data and interviews. This study applies Paul Ricour’s Hermeneutic approach which is conducted through appreciation of symbols to the idea of ‘thinking of’ symbols. Ricour considers that hermeneutics is a way to explore hidden meanings in texts that appear to contain meaning, also an atempt to fght against “cultural distortion”, through semantics, re?ection, and existential or ontological.Keywords: Avant-Garde, Artwear, Dewi Sri.